2019
DOI: 10.1080/09575146.2019.1655713
|View full text |Cite
|
Sign up to set email alerts
|

A gendered contribution to play? Perceptions of Early Childhood Education and Care (ECEC) practitioners in England on how their gender influences their approaches to play

Abstract: There is a persistent suggestion that the lack of men who choose to work with young children (0-5 years) is detrimental to children's learning and development. This study analysed whether practitioners believed that men who work with young children adopt specific approaches within a play pedagogy. Practitioner beliefs about how their gender influences their practices were gathered through qualitative surveys and open-ended, photo-based interviews. This paper argues practitioners use conflicting scripts to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Of further note is the term gender equality whose primary goal is gender neutral citizenship, in which women are allowed to participate with men as equal citizens, especially in the public sphere, and the fact that no research has yet explored the predictive power of student achievement. based on gender (Josephidou, 2020;Ugwuanyi et al, 2020;Woehrle et al, 2011). Gender equality is like a "holy" expression (term) that is often used by social activists, feminists, politicians, and even almost by state officials (Effendi & Ratnasari, 2018;Fraile & Gomez, 2017;Subašić et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Of further note is the term gender equality whose primary goal is gender neutral citizenship, in which women are allowed to participate with men as equal citizens, especially in the public sphere, and the fact that no research has yet explored the predictive power of student achievement. based on gender (Josephidou, 2020;Ugwuanyi et al, 2020;Woehrle et al, 2011). Gender equality is like a "holy" expression (term) that is often used by social activists, feminists, politicians, and even almost by state officials (Effendi & Ratnasari, 2018;Fraile & Gomez, 2017;Subašić et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hogan (2012) found that her teacher trainees were 'gender blind', believed that 'gender in early childhood education is largely unproblematic' (2012, 1) and showed a resistant attitude to examining gender critically. However, currently, a growing body of researchers is calling for teacher preparation courses to include gender sensitisation training and create a more gender-conscious workforce (Peeters et al, 2015;Josephidou, 2018;Warin, 2018). Some authors argue strongly that trainers should be willing to examine and discuss their own gendered assumptions before expecting their trainee students to undertake this kind of consciousness raising (Lenz Taguchi, 2005;Burn and Prat-Adams, 2015).…”
Section: Support (Practical and Theoretical) For Eye Staffmentioning
confidence: 99%
“…Young children tend to be left to play alone in the schoolyard. Game stimulation that aims to improve language development is given without apparent readiness and goals so that they cannot achieve their target language (Dong et al, 2020;Josephidou, 2020;Vartiainen & Kumpulainen, 2020). Based on this, it can be concluded that the stimulation of receptive and productive language development is rarely done using exciting media.…”
Section: Introductionmentioning
confidence: 99%